A Signature of Nine lncRNA Methylated Genes Predicts Survival in Patients With Glioma - Cheng, Meng; Sun, Libo; Huang, Kebing; Yue, Xiaoyu; Chen, Jie; Zhang, Zhengwei; Zhao, Bing; Bian, Erbao (Frontiers in Oncology, 2021)
Glioma is one of the most common malignant tumors of the central nervous system, and its prognosis is extremely poor. Aberrant methylation of lncRNA promoter region is significantly associated with the prognosis of glioma patients. In this study, we investigated the potential impact of methylation of lncRNA promoter region in glioma patients to establish a signature of 9 lncRNA methylated genes for determining glioma patient prognosis. Methylation data and clinical follow-up data were obtained from The Cancer Genome Atlas (TCGA). The multistep screening strategy identified 9 lncRNA methylated genes that were significantly associated with the overall survival of glioma patients. Subsequently, we constructed a risk signature that containing 9 lncRNA methylated genes. The risk signature successfully divided the glioma patients into high-risk and low-risk groups. Compared with the low-risk group, the high-risk group had a worse prognosis, higher glioma grade, and older age. Furthermore, we identified 2 lncRNAs termed PCBP1-AS1 and LINC02875 that may be involved in the malignant progression of glioma cells by using the TCGA database. Loss-of-function assays confirmed that knockdown of PCBP1-AS1 and LINC02875 inhibited the proliferation, migration, and invasion of glioma cells. Therefore, the 9 lncRNA methylated genes signature may provide a novel predictor and therapeutic target for glioma patients.